Sex hormones and cancer. - Key, T; Beral, V (1992)
There are few instances in which a clear effect of hormones on cancer risk is known and in which the effects of those hormones on the cells concerned are also known. The best examples are the relationships between sex hormones and cancer in women. The effects of sex hormones both on the risk for endometrial cancer and on the cells of the endometrium are well understood, and the evidence strongly suggests that hormones act by altering the rate of cell division. The same mechanism may explain the relationships between sex hormones and the risk for breast cancer, but our understanding of cancers at this site is incomplete. Less still is known about the mechanisms of the effects of sex hormones on other hormone-related cancers, such as those of the ovary and cervix. Most sex hormones are not genotoxic.